2012
DOI: 10.1007/s00296-011-2337-5
|View full text |Cite
|
Sign up to set email alerts
|

Maximal locomotor depression follows maximal ankle swelling during the progression of arthritis in K/BxN mice

Abstract: It is well established that arthritis depresses locomotion in humans as well as in animal disease models. The K/BxN mouse model resembles rheumatoid arthritis and is widely used for research. Here, we investigate the behavioral alterations of arthritic K/BxN mice during arthritis development with respect to horizontal locomotion. Locomotor activity measurements and the methodology of ankle thickness measurements are compared to demonstrate the feasibility of motion tracking in the K/BxN mouse model. Arthritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Rajasekaran et al[ 66 ] observed maximum decline in locomotor activity during the period when peak joint thickness occurred in the arthritic mice. Similar observation was made by Frommholz and Illges [ 67 ] who also showed an indirect correlation of ankle thickness and locomotor activity in arthritic K/BxN mice. Our study also demonstrates similar correlation between oedema scoring of infected limb and locomotion counts.…”
Section: Discussionsupporting
confidence: 89%
“…Rajasekaran et al[ 66 ] observed maximum decline in locomotor activity during the period when peak joint thickness occurred in the arthritic mice. Similar observation was made by Frommholz and Illges [ 67 ] who also showed an indirect correlation of ankle thickness and locomotor activity in arthritic K/BxN mice. Our study also demonstrates similar correlation between oedema scoring of infected limb and locomotion counts.…”
Section: Discussionsupporting
confidence: 89%
“…Inflammation and suppression of pain-related spontaneous behaviors, such as locomotor activity, operant responses, and place avoidance, are strongly correlated in rapid-onset models of arthritis [134]. However, the more slowly progressing K/BxN mouse strain shows a significant delay between peak clinical progression and decreased mobility [178]. This finding is suggestive of a psychoaffective component to pain-suppressed behaviors, which is commonly observed in human RA.…”
Section: Understanding the Molecular Mechanism Underlying The Pathogementioning
confidence: 94%
“…The appraisal of horizontal locomotion was evaluated by the method of Frommholz et al The mice underwent an adapting phase of 5 minutes and were then recorded for 10 minutes. The actual motion tracking was done with SwisTrack (École Polytechnique Fédérale de Lausanne, Switzerland).…”
Section: Methodsmentioning
confidence: 99%